ToucheGreen : surround sound artwork - Soh, Sandra Tein Sin (2016)
This report presents the work leading to TouchéGreen, an interactive surround sound installation. It is a platform for people to interact with a living plant. This report is divided into three phases: singing plant, convolution of audio input from people and plant, and the presentation of the installation. In each phase of the project, iterative and explorative approaches were taken to find the ideal methods. This report will start with an introduction of the project, which is categorised in motivation, objectives and set-up. Following will be the literature review that provides information about the software and hardware used in this project, research done in related subjects, such as convolution and Touché frequency principle, and relevant work done. Next section includes various researches and experiments taken for each phase. Each approach is subdivided in three parts: aims, method, and results. A final set-up with selected approaches is done and is described in detail in the following chapter. Result and Evaluation will be discussing aims achieved, drawback and reasons that caused it. This report will end with a conclusion to summarise the work done in the past year, with suggested future improvement on TouchéGreen. Project No: B3417-151 ￼￼